Malik-Militancy Conundrum: Deciphering the Transitions in Traditional Pakhtun Leadership - Aman, Shahida (Islamic Studies, 2013)
By exploring the case study of militancy in Bara, Khyber Agency in Pakistan’s Federally Administered Tribal Areas (FATA), this paper investigates the emergence of militant leadership and attempts to locate it in the leadership categories of Pakhtuns, identified by the literature. It further traces the impact of the rise of alternate leadership in Bara, Khyber Agency as affecting the leadership roles and responsibilities of traditional Pakhtun leadership categories of maliks (village headmen) and mashars (lungi or stipend holders, sufaid raish/spin giri or white bearded, elders). The main findings of this paper suggest that the rise of alternate militant leadership has created a clear diminution in the leadership roles and responsibilities of maliks and mashars in Bara, Khyber Agency, which in turn has affected other traditional structures of governance, such as jirgah (council of elders) and the traditions of Pakhtunwali (Pakhtun code of life), which govern the Pakhtun way of life in the tribal areas. It emphasises that leadership transformations in Pakhtun society need to be analysed not only within the paradigm of ongoing militancy, but also emanating from state’s slow inroads into FATA through reforms and the emergence of new business elite as a result of trade and transnational movement of goods in grey and black markets. This paper further argues that the categorisation of the current militant leadership as religious poses complexities. It is because the current leadership of Lashkar-i Islam, the militant tanzeem (group) of Bara, is not madrasah (religious seminary) educated and therefore cannot be categorised A'alim (religious scholar) or pir (holy man) in the religious or traditional sense of the term, but it seeks legitimacy on religious grounds and on the power of shari'ah implementation. There is also a strong tribal element of support here as Lashkar-i Islam mostly recruits from Sepah khel (sub-tribe, clan) of the Afridi tribe in Khyber Agency’s Bara tehsil (administrative sub-division). Lacking a formal training in Islamic madrasah education and engaged in an armed violent struggle, such leadership, therefore, may also be termed a petty warlike chief of their tanzeem or militant outfit. Here one sees intermingling of religion, culture and tribal support to create a legitimacy basis for the militant leadership.